Pengaruh Number Head Together dan Motivasi Belajar terhadap Prestasi Siswa - Nike Yuli Restina Manurung; Ayi Darmaya; Dodi Sukmayadi (Mahesa Research Center, 2022)
This article aims to determine the effect of the Number Head Together type of cooperative learning model on student achievement, the effect of motivational learning on learning achievement, the effect of NHT model interaction and learning motivation on student achievement. This research was conducted at SDN 112233 Sidorejo, Torgamba District. The population was all 60 fourth grade students. The sample is all students as many as 30 students in class A and as many as 30 students in class B. The research instruments used were learning outcomes tests and learning motivation questionnaires. The research method uses a quasi-experimental method with a 2x2 factorial. The data analysis technique used ANOVA at a significant level of 0.05. The results of the analysis show that the learning achievement of students with the NHT model is higher than those taught by the conventional model (Fcount = 11,619> Ftable = 2.0021), there is a significant difference in the learning outcomes of students who have high motivation and low motivation (Fcount = 15,646> Ftable = 2 0.0021) and there is a significant interaction between the NHT model and students' learning motivation on learning achievement (Fcount = 4.378> Ftable = 2.0021). This study concludes that overall students who are taught with the NHT cooperative learning model and have high motivation have higher learning achievements than students who are taught using the conventional model